Teaching social justice through Shakespeare : why Renaissance literature matters now - Eklund, Hillary Caroline, 1977-; Hyman, Wendy Beth (Edinburgh University Press, 2019)
Provides diverse perspectives on Shakespeare and early modern literature that engage innovation, collaboration, and forward-looking practices.